Household food waste separation behavior and the importance of convenience - Bernstad, Anna (Waste management (Elmsford), 2014)
•Written information about food waste recycling did not increase source-separation ratio.•Installation of equipment for separate collection of food waste in kitchens increased source-separation.•Convenience for sorting of food waste inside the very household must be addressed. Two different strategies aiming at increasing household source-separation of food waste were assessed through a case-study in a Swedish residential area (a) use of written information, distributed as leaflets amongst households and (b) installation of equipment for source-segregation of waste with the aim of increasing convenience food waste sorting in kitchens. Weightings of separately collected food waste before and after distribution of written information suggest that this resulted in neither a significant increased amount of separately collected food waste, nor an increased source-separation ratio. After installation of sorting equipment in households, both the amount of separately collected food waste as well as the source-separation ratio increased vastly. Long-term monitoring shows that results where longstanding. Results emphasize the importance of convenience and existence of infrastructure necessary for source-segregation of waste as important factors for household waste recycling, but also highlight the need of addressing these aspects where waste is generated, i.e. already inside the household.